Kitsch : History, Theory, Practice - Monica Kjellman-Chapin (Cambridge Scholars Publishing, 2020)
Kitsch: the mere word evokes mental images of cutesy collectibles, treacly trinkets, sweetly sentimental scenes, thematically trite tabletop tchotchkes, or perhaps anemic appropriations of canonical works of art. Frequently dismissed as facile, lowbrow, or one-off, throwaway aesthetics, kitsch elicits responses that range from the sardonic smirk laced with derision to the grin glimmering with the indulgence in a ""guilty"" pleasure. Kitsch, however, is surprisingly mobile and complex, as evidenced by its recent renewal as ""kitschy cool."" This ambiguity not only allows it to gesture towards a.